Pharmacy-based initiatives to reduce unintended pregnancies: A scoping review - Buckingham, Pip; Amos, Natalie; Hussainy, Safeera Y.; Mazza, Danielle (Research in social and administrative pharmacy, 2021)
Community pharmacy contraception services are thought to improve access, with the potential to reduce the persistent sexual and reproductive health inequities observed globally. We aimed to identify the range of pharmacy-based initiatives addressing unintended pregnancy in the primary literature and examine their feasibility, acceptability and effectiveness. Using the Joanna Briggs Institute Methodology for Scoping Reviews, we searched seven bibliographic databases using combinations of keywords and subject headings for related to contraception and community pharmacy. Studies of any design undertaken in high income countries for reproductive-aged women were eligible provided they evaluated intervention or legislation after the implementation of these initiatives. Included articles were critically appraised and findings summarised narratively. We identified 49 articles, 80% of which involved pharmacist supply of emergency contraception (EC), 14% of regular contraception methods, and 6% involved adjuncts of EC dispensing: counselling (2%) and bridging initiatives to link clients with regular contraception (4%). EC initiatives were perceived as feasible and were facilitated by interdisciplinary partnerships but there are persistent barriers to the provision of initiatives congruous with the retail pharmacy setting. Furthermore, consumers may be reluctant to receive contraceptive counselling from pharmacists but often value the convenience and anonymity pharmacy services offer. Overall, interventions improved access to contraceptive products but did not consistently reduce inequities, and the health benefits of pharmacy initiatives are either small (EC) or lacking description in the literature (other contraceptive methods and contraceptive counselling). Pharmacy initiatives may not negate all barriers to access or reduce unintended pregnancy rates, however they are valued by pharmacists and consumers. Evidence gaps including the lack of description of health outcomes of regular contraception provision, contraceptive counselling and the perceived barriers and facilitators of access and provision from end-user perspectives, should be pursued in future research, to establish initiatives’ utility and effectiveness.